Noma management in a 47-years-old female patient using estlander flap: a case report - Anak Agung Bagus Satria Brahmananta; Ida Bagus Adiguna Wibawa; Anak Agung Ngurah Asmarajaya (DiscoverSys Inc., 2020)
Background: Noma or cancrum oris is an uncommon disease that results in loss of tissue in the oronasal region secondary to gangrenous slough. As most patients with noma do not report until the disease is at an advanced stage, its onset and progression remain a mystery. Survivors of this disease suffer severe facial deformity due to loss of facial tissues and scarring. Reconstruction of such type of defects was aimed to maintain oral competence, sufficient oral access, and preservation of sensation.Case: A woman, 47 years old, experience with a chief complaint of the deformed right upper lip for the past 45 years. The patient is known to have a history of deformity on the right upper lip region when the patient was two years old. The patient stated that it originally started with swelling on the right cheek accompanied by redness and painful sensation.Result: An extensive scar along with half of the upper lip missing was found in the physical examination, causing exposure of anterior maxillary teeth. A full-thickness defect of half of the upper lip with severe scar contracture was also found in the further examination, thereby constricting the oris. The patient was planned for surgical management under general anesthesia. Lip reconstruction using an Estlander flap was done.Conclusion: Reconstruction must be planned carefully to restore the natural contours of the lip. The Estlander flap is one of the treatment choices used for labial defects that include the commissure.